Video call or chat? Negotiation of meaning and issues of face in telecollaboration - van der Zwaard, Rose; Bannink, Anne (System (Linköping), 2014)
In an attempt to evaluate the influence of the type of digital medium on language learner communication, this study examines negotiation of meaning during interaction between native speakers and non-native speakers of English in a task-based advanced second language classroom via two forms of real-time one-to-one computer-mediated communication: video calling and instant chat-messaging. It investigates the nature, scope, and possible patterns of negotiated interaction in both types of digital communication modes. Dyadic groups consisting of non-native speakers and native speakers from two different universities collaborated in a series of one-to-one digital real-time interchanges. The digital discourse produced during the telecollaboration sessions was analysed within the framework of the negotiation of meaning theory, following the Varonis and Gass model of non-understandings (1985). It was found that negotiation of meaning episodes occurred in both types of real-time interaction but that they yielded their own distinct patterns of negotiated interaction. The data suggest that communication through video calling triggers more potential loss of face issues for the second language learner than communication through chat, which has a direct effect on the trajectory and outcome of the interactions.